2013
DOI: 10.1186/1471-2431-13-66
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and practices regarding childhood fever among parents: a cross-sectional study from Palestine

Abstract: BackgroundFever is an extremely common occurrence in paediatric patients and the most common cause for a child to be taken to the doctor. The literature indicates that parents have too many misconceptions and conflicting information about fever management. The aim of this study was to identify parents’ beliefs and practices regarding childhood fever management.MethodsWe conducted a cross-sectional survey among parents whose children were enrolled and presented for health care at primary health care clinics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 29 publications
5
60
0
19
Order By: Relevance
“…The present study revealed that almost most of the caregiver doesn't use the thermometer for checking child temperature. The result of the study was supported by the cross-sectional study conducted by Zyoud, which showed that around two thirds of parents recognize fever in their children by non-measurement methods such as observing, by touching the child and only 31.6% measure the temperature [12].…”
Section: Discussionmentioning
confidence: 49%
“…The present study revealed that almost most of the caregiver doesn't use the thermometer for checking child temperature. The result of the study was supported by the cross-sectional study conducted by Zyoud, which showed that around two thirds of parents recognize fever in their children by non-measurement methods such as observing, by touching the child and only 31.6% measure the temperature [12].…”
Section: Discussionmentioning
confidence: 49%
“…Similarly in a Palestine study 61% of parents used thermometer to detect fever. 5 In his study more than 50% of parents were graduates and it was found that knowledge of temperature measurement do significantly vary with education of parents (P=0.001). Education and mass awareness also affected the knowledge regarding time duration for keeping thermometer at axila.…”
Section: Awarenessmentioning
confidence: 92%
“…1,2,4,5 Misconceptions about the dangers of fever are common. Unwanted fears about harm from fever causes lost sleep and unnecessary stress for many parents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations